Implementation of MBKM Teaching Assistance Program in Improving Teacher Digital Literacy in Aceh Besar District - Azis, Daska; Furqan, M Hafizul; Sinaga, Rizky (Al-Khawarizmi, 2023)
The Teaching Assistance Program is a program initiated by the government through Kemendikbudristekdikti. This program aims to provide opportunities for students to sharpen competencies in the 21st century. The formulation of the problem in this research is, what is the level of digital literacy of teachers in schools implementing the MBKM Teaching Assistance Program in Aceh Besar District? This research uses descriptive analysis method. The population of this study were 15 tutors spread across 14 schools in Aceh Besar. Data collection was carried out by distributing questionnaires to respondents, then the data were analyzed using simple statistical formulas. The results of the research on the level of digital literacy of teachers in schools implementing the MBKM Teaching Assistance Program in Aceh Besar District, namely very high category 6.66%, high category 20%, medium category 60%, low category 6.66%, very low category 6.66% . In general, the level of digital literacy of teachers in schools implementing the MBKM Teaching Assistance Program in Aceh Besar is in the moderate category.